Production of Food – Grade Liquid Smoke from Candlenut Shell through a Consecutive Pyrolysis – Distillation Process - Sulhatun Sulhatun; Faisal Faisal; Satria Nanda; Syarifah Akmal; Tubagus Rayyan Fitra Sinuhaji (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2025)
Concerning the increasing demand for food-grade liquid smoke, this research focuses on liquid smoke purification through distillation to improve quality, in terms of color, odor, and chemical composition, while eliminating carcinogenic compounds such as tar residues. For that reason, this study aims to investigate the production of liquid smoke from candlenut shells using a 300 kg capacity pyrolizer. Pyrolysis was conducted at 350 – 400°C for 1 – 6 hours to produce liquid smoke. Distillation temperature and time were varied to examine their effect on liquid smoke quality. Based on the phenol content, an optimal pyrolysis condition was achieved at temperatures between 350 and 450°C for 3.5 hours from which the highest phenol content value (56.76% w/w) was obtained. In addition, distillation at 200°C for 40 minutes resulted in the highest distillate yield of 38.74% w/w, which corresponds to a phenol content of 73.42% w/w. Furthermore, heavy metal contamination tests revealed that mercury, arsenic, cadmium, and lead levels were well below their maximum tolerable limit for food additives. These results demonstrate that the distillation condition significantly influences the quality and yield of liquid smoke.